Analisis Tindak Tutur Direktif Bahasa Dayak Pantu 100 Desa Temiang Sawi Kabupaten Landak Kalimantan Barat - Ayu, Ayu; Wulan, Adisti Primi; Hajjafiani, Dini (LPPM STKIP PGRI Bandar Lampung, 2024)
The purpose of this study is to characterize directed speech actions in 100 Temiang Sawi Villages, Landak Regency, using the Dayak Pantu language. Pragmatics is the subject of inquiry. The study was conducted in Temiang Sawi Village, Ngabang District, Landak Regency, using a descriptive, qualitative research design. The data source in this research is the native Dayak Pantu language speaking community from 100 Temiang Sawi Village, Landak Regency. Data collection techniques and tools, direct communication techniques, listening techniques, skillful involvement with data collection tools, namely recording devices, data cards and documentation. Data collection, data reduction, data presentation, and inference from the data outcomes are all steps in the data analysis process. Furthermore, the data found in the research are four types of directive speech act data, namely ordering, ordering, begging and giving advice. The total amount of data on commands, orders, requests and suggestions was tens of data found. Command forms the words to ask, order, call, suggest, hope. Ordered forms of the words instructions and advice. Invoke soft and rough word forms. Providing suggestions on the form of words for opinions, suggestions and recommendations.